Pendekatan Sistem Dalam Teori Hukum Islam (Perspektif Jasser Auda) - Ilham Mashuri (IAIN Padangsidimpuan, 2019)
The main problem in the development of Islamic law is the failure to distinguish between nash and tafsir, strong atomistic approach, and binary. Instead of contributing to the contemporary problems, it is confined in right or wrong polemic, cause and effect, qath’i zhani, male and Female; rejecting the role of other sciences (science, social science, philosophy) in the development of Islamic law. Through a system approach, Jasser Auda offers a “multidimensional” approach and a more holistic approach. The Auda’s system approach is in line with the objectives of Islamic law or realizing the maqasid by maintaining openness, renewal, and even the validity of ijtihad must be measured to the extent that it realizes the maqasid.